Princeton Essays in International Finance - Kindleberger, Charles P. (Journal of Economic Literature, 1969)
AMPHLETS pose bibliographical problems. The system of scholarly production and consumption is geared easily and smoothly to books and articles, but pamphlets fall between. for example, are reviewed, and articles may be the subject of published comment, reply, rejoinder, final comment and the like. Pamphlets live on after their appearance mainly in footnote citation-which the scholarly apparatus has yet to measure and weigh. An occasional professional periodical like the Economic Journal will list pamphlets by title under Recent Periodicals and Books, and even include a sentence or two of description in 6-point type. Paul Einzig reviewed essays by A. K. Swoboda and F. H. Klopstock on Euro-dollars (Nos. 64 and 65 in Essays) in the Economic Journal for March 1969. But this is rare. For the most part pamphlets are left to drop into the pool of scholarship and swim by themselves if they can. To repair a little of this neglect, this review article addresses the Princeton Essays (plus Studies, Special Papers and Reprints) in International Finance, not to call attention to them, since they are well known, but to celebrate the appearance of the 75th Essay in a series going back to 1943, and perhaps the 40th or 41st in the last 8Jl years under the brilliant editorship of Professor Fritz Machlup. There is far too much to talk about in 3,000 words or less-changing the gold price, seigniorage in international asset creation, crawling pegs, bands, forward exchange, foreign aid, liquidity and the rest. If one went back to the 1950s, one would find more trade, and somewhat less finance, but oil, merchant-marine policies, international cost-sharing and agriculture price policy. There are too many memorable essays; to cite only a few is invidious but inescapable. This exercise is accordingly addressed mainly to bibliographical or bibliophilic issues raised by the series, and only tangentially to substance. Pamphlets are expensive for librarians. They must be accessioned (should the phrase be acceded to?) and catalogued at an average cost of several dollars an item, much higher a rate per page of scholarship than books, because of the lumpiness of the process. This is because they are not indexed with joumal articles. In a curriculum vitae pamphlets belong under articles, in the library apparatus under books. But not all retrieval apparatus will cope with pamphlets on the same basis as books: the AEA Periodical Index will do well to include the standard series of pamphlets, such as the Essays, Studies, Special Papers in its special volume for lost literature-an index of articles in Festschriften, symposia, conference proceedings. The library problem aside, what of the scholar? Should he file his Essays alphabeti cally by author in the vertical files housing reprints in his outer office, or shelve them in the inner sanctum with books? A survey